AGRICULTURAL TRANSFORMATION AGENDA AND THE ATTAINMENT OF SUSTAINABLE DEVELOPMENT GOALS 1 AND 2 IN NIGERIA: A STUDY OF FADAMA III ADDITIONAL FINANCING FOR RICE PRODUCTION IN ENUGU STATE - Stephen Nwachukwu, Tochukwu; Isah, Abdulrouf; Thomas Ogbaga, Sunday; Omumu Anyadike, Nkechinyere (International Journal of Psychosocial Rehabilitation, 2021)
Agriculture was the bedrock of food security and a means of sustainable development in Nigeria in the pre- and post-independence era, until the 1970s, during the emergency of the oil boom in Nigeria. The unprecedented rise and consequent sale of the product pushed Nigeria away from agriculture to oil there by leading to unimaginable neglect and abandonment of her mighty man of valour. These abandonments led to an increased decline in food security and sustainable development, thereby a continuous increase in poverty and hunger until the federal government, through agricultural reform programs, decided to resuscitate the sector with the introduction of an agricultural transformation agenda. Using the multistage research methodology and evaluation theory, this study is aimed at assessing the agricultural transformation agenda policy contribution towards the eradication of hunger and poverty in Nigeria using Fadama III additional funding (AF) for rice production in Enugu State. The researcher found out that the World Bank gave out $200 million in grants to Nigeria, of which Enugu State got $13,550,215.08. Which is N3,550,143,817.76 in naira, the reform drastically reduced hunger and poverty through the assistance given by the Enugu-State government. Inferring from the above, the researcher recommended the appointment of a farmer who could be able to understand the body language of their colleagues and proffer solutions. The research concluded with a call to stakeholders to hasten up efforts towards agricultural transformation in Nigeria.